Does integrated conservation of terrestrial orchids work? - Swarts, Nigel; Batty, Andrew; Hopper, Stephen; Dixon, Kingsley (Lankesteriana: International Journal on Orchidology, 2015)
Effective plant conservation involves careful con- sideration and difficult choices when investing limit- ed resources to conservation programs and policies. The conservation practice must integrate the under- standing of existing and future environmental threats, taxonomic distinctiveness, numbers of individuals in populations, reproductive biology, ex situ propagation and the maintenance of evolutionary processes influ- encing population distribution patterns.